Rickettsia parkeri in Amblyomma maculatum Ticks, North Carolina, USA, 2009–2010 - Andrea S. Varela-Stokes; Christopher D. Paddock; Barry Engber; Marcee Toliver (Emerging Infectious Diseases, 2011)
We detected Rickettsia parkeri in 20%−33% of Amblyomma maculatum ticks sampled in North Carolina. Results highlight the high frequencies of R. parkeri–infected ticks in the state with the highest annual incidence of Rocky Mountain spotted fever. Epidemiologic studies are needed to definitively link R. parkeri to cases of spotted fever rickettsiosis.